Studies of morisita's index of dispersion and chi square (X2) of nepenthes species at different altitude on Gunung Pulai, Johore / Liliwirianis Nawi and Nor Lailatul Wahidah Musa - Nawi, Liliwirianis; Musa, Nor Lailatul Wahidah (2011)
Four species of Pitcher plants, namely Nepenthes ampullaria, N gracilis, N x hookeriana and N rafflesiana were recorded on Mt.Pulai. The distribution of pitcher plants according to altitude on the mountain slope was found to differ between the species recorded. Nepenthes rafflesiana was found at all elevations that is 150 m, 500 m, 550 m and 600 m. N ampullaria was recorded at 500 m, 550 m, and 600 m. Nepenthes gracilis was present at 500 m, 550 m and Nx hookeriana was recorded at 550 m only. The population dispersion pattern of Nepenthes rafflesiana and N x hookeriana seedlings and matures plants N ampullaria and N gracilis were contagious. Mature plants saplings of N rafflesiana, seedlings of N. ampullaria and saplings of N gracilis were random and contagious.